Neuropsychology and Neuropsychiatry of Neurodegenerative Disorders - Manuel Menendez-Gonzalez (Frontiers Research Topics, 2016)
This book compiles all articles within the Research Topic "Neuropsychology and neuropsychiatry of neurodegenerative disorders" published in the journal Frontiers in Aging Neuroscience. The call was launched in 2014 and closed in 2015 with 21 articles published. Papers deal on several important topics of neuropsychology -such as language and visuospatial functions- and neuropsychiatry - such us the emotional or motivational spheres - , and the interphase between them. There are also articles on psychometry, brain morphometry, brain connectivity, diagnostic tests and interventional studies. All these articles are focused on neurodegenerative conditions, mostly Alzheimer’s disease and Parkinson’s disease. Interestingly, several articles addressed the early stages of these diseases. All together, this Research Topic provides a rich perspective of the research made today around neuropsychological and neuropsychiatric aspects of neurodegenerative diseases. We hope readers enjoy this collection of articles.